Digital Resistance to Asian-American Hate during COVID-19: Study of Photography and Art on Instagram - Narayanamoorthy, Nanditha (Imaginations, 2023)
In this research, I study the digital resistance to Asian-American hate, isolation, alienation, and ‘othering’ visibilized during the COVID-19 pandemic in 2020-21 in the Global North. Specifically, I draw attention to the role of personal and artistic representations of Asian female bodies that perform both a resistance to hate, in the context of the pandemic, and an affirmation of ethnic and racial heritage and belonging of the self in North America. Through the engagement with #stopasianhate and #haterisavirus hashtags on Instagram, I uncover the rejection of historic and contemporary racial and gendered violence, harassment, xenophobia, and othering that emerges through visual activism and personal and artistic performativity online. I focus on the interplay between body politics and anti-racist feminist digital activism in order to understand how performativity of the self through photography and art can empower Asian-American female bodies.